Reexamining Fear Appeal Models from Cognitive Appraisal Theory and Functional Emotion Theory Perspectives. Issue 1 (2nd January 2016) - So, Jiyeon; Kuang, Kai; Cho, Hyunyi
Abstract : Recognizing inconsistencies between the extant fear appeal theories and emotion literature, this research integrated cognitive appraisal theory and functional emotion theory into a fear appeal literature and proposed a model that describes a process through which both fear and anxiety can contribute to adaptive responses. Findings from an experiment ( N = 927) supported the predictions. Fear and anxiety emerged as distinct constructs. Perceived susceptibility was a stronger predictor of anxiety than fear, while perceived severity was a stronger predictor of fear than anxiety. In addition, greater fear and anxiety led to greater response efficacy through increased motivation to obtain protection-related information and heightened attention to such information, thus mediating the threat and coping appraisal processes. The SEM model testing the predictions showed that perceived susceptibility had the strongest total effects on protection intention, followed by anxiety, perceived severity, and fear.